Nonfatal Assault Injury Trends in California, 2005 to 2015 - Rowe, Christopher L. (Journal of interpersonal violence, 2021)
Interpersonal violence is a major global public health problem, and the burden of nonfatal assault injuries is far greater than that of homicides. To understand trends and inform prevention priorities, we sought to describe nonfatal assault injury trends across demographic groups from 2005 to 2015 in California, USA. Comprehensive hospitalization and emergency department discharge records were used to estimate annual rates of nonfatal assault injury overall and by means and age group and age-standardized annual rates by race/ethnicity, gender, and county. The overall rate of assault injury was stable in California from 2005 to 2015 (mean = 364 per 100,000), but there was substantial heterogeneity across demographic groups, including increases among African Americans (900 to 1,194), American Indian/Alaskan Natives (423 to 572), older individuals (age 25-29 = 697 to 727; 30-39 = 495 to 557; 40-49 = 352 to 404; 50-59 = 194 to 313; 60+ = 66 to 106), and women (199 to 252). Assault injury rates increased among several demographic groups, warranting the attention of professionals involved in violence prevention efforts. Epidemiologic examination to better understand causes of increases can inform prevention efforts. Similar analyses should be applied to other settings to determine how broadly these patterns are observed.